Adoptive transfer of regulatory T cells promotes intestinal tumorigenesis and is associated with decreased NK cells and IL‐22 binding protein. Issue 10 (5th May 2014) - Janakiram, Naveena B.; Mohammed, Altaf; Bryant, Taylor; Brewer, Misty; Biddick, Laura; Lightfoot, Stan; Lang, Mark L.; Rao, Chinthalapally V.
Abstract : High number of regulatory T cells (Tregs), both circulating and at the tumor site, often indicates a poor prognosis in CRC patient's possibly impairing natural killer (NK) cell function. To determine the role of Tregs in CRC development and their effects on NK cells, we created novel transgenic Rag‐Apc mice that lack T cells and develop spontaneous intestinal tumors, and we adoptively transferred Tregs or transiently depleted NK cells during initial stages of tumorigenesis. In 6‐weeks old Rag‐Apc mice containing microscopic intestinal tumors adoptive transfer of Tregs or transient NK cell depletion dramatically associated with an increase in intestinal tumor multiplicity and tumor size, with significantly decreased survival rates. Importantly, Treg transfer increased small intestinal polyp formation up to 65% ( P  < 0.0005) and increased colon tumors multiplicities by 84% ( P  < 0.0001) with a significant decrease in NK cells as compared to control mice. Similarly, in NK depleted mice, colon tumor multiplicities increased up to 40% and small intestinal polyp formation up to 60% ( P  < 0.0001). Treg transfer or NK cell transient depletion markedly increased interleukin (IL)‐22 systemically and the inflammatory signaling molecules P2X7R, and STAT3 in the tumors; and impaired production of the tumor suppressor interferon (IFN)‐γ systemically. Notably, IL‐22 binding protein (IL‐22 BP) was associated with NKs and a significant decrease was seen at the tumor site in mice adoptively transferred with Tregs or depleted of NK cells. Our results suggest that adoptive transfer of Tregs aggressively promote intestinal tumorigenesis by decreasing NK cell number and activity by modulating IL‐22 BP. © 2014 Wiley Periodicals, Inc.